The Generalizability of Patients' Preferences and Concerns regarding Anesthesia Care for Cesarean Delivery: A Prospective Survey. (2nd December 2021) - Smith, Aaron J.; Daly, Jaime; Arnolds, David E.; Scavone, Barbara M.; Carvalho, Brendan
Abstract : Background . False assumptions regarding the generalizability of patients' expectations and preferences across different demographic groups may contribute in part to the increased prevalence of negative peripartum outcomes seen among women of color. The intention of this study was to determine preferences and concerns regarding anesthesia care during cesarean delivery in a largely African-American population and to compare them to those obtained in a prior study conducted in a demographically distinct population. Methods . Women presenting for scheduled cesarean delivery or induction of labor completed a preoperative survey requesting demographic information and the opportunity to rank ten common potential anesthetic outcomes in relation to each other from most to least desirable. Participants were also asked about their biggest fear concerning their anesthetic and their preferences and expectations regarding degree of wakefulness, pain, and other adverse events. Those who underwent cesarean delivery were administered a briefer postoperative survey. We tabulated preference rankings and then compared demographic and outcome data to that obtained in a previous study with a demographically dissimilar population. Results . A total of 73 women completed the preoperative survey, and 64 took the postoperative survey. Pain during and after cesarean delivery was ranked as least desirable outcomes and fear of paralysis was respondents' principal concern with neuraxial anesthesia. Postoperative concerns were similar to preoperative concerns and did not correlate with the frequency with which specific adverse outcomes occurred. These results were consistent with those from the previous study despite the women in this study being more likely to be younger, unmarried, African-American, and less educated than those in the previous investigation. Conclusions . Patient preference rankings and concerns were remarkably similar to those previously demonstrated despite a number of demographic differences between the two populations, suggesting generalizability of these preferences to a broader obstetric population.